2011
DOI: 10.1007/s00221-011-2914-6
|View full text |Cite
|
Sign up to set email alerts
|

Text-speak processing and the sustained attention to response task

Abstract: We examined performance in a sustained attention to response task (SART) (Experiment 1) and a more traditionally formatted vigilance task (Experiment 2) using novel word stimuli (text-speak) and normally spelt words. This enabled us to address whether the SART is a better measure of sustained attention or of response strategy, and to investigate the cognitive demands of text-speak processing. In Experiment 1, 72 participants completed a subset (text-speak) and a word SART, as well as a self-reported text exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Also relevant is the finding that sustained attention performance in the SART, as measured by a reduction in errors, improves with age, but this error reduction is entirely accounted for by robust response slowing with increasing age . In accordance with these findings, Head, Russell, Dorahy, Neumann, and Helton (2012) recently reported that participants who were proficient in text-speak were more inclined to respond quickly to a text-speak variant of the SART, but that these participants were also more inclined to produce a greater number of commission errors. Such changes in performance appear to reflect adjustments in response strategies to deal with attention-demanding tasks, rather than modifications of attentional ability per se.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Also relevant is the finding that sustained attention performance in the SART, as measured by a reduction in errors, improves with age, but this error reduction is entirely accounted for by robust response slowing with increasing age . In accordance with these findings, Head, Russell, Dorahy, Neumann, and Helton (2012) recently reported that participants who were proficient in text-speak were more inclined to respond quickly to a text-speak variant of the SART, but that these participants were also more inclined to produce a greater number of commission errors. Such changes in performance appear to reflect adjustments in response strategies to deal with attention-demanding tasks, rather than modifications of attentional ability per se.…”
supporting
confidence: 55%
“…That is, it has been observed that when participants speed up, they make more errors, and when they slow down, they make fewer errors (e.g., Head et al, 2012;Helton et al, 2009;Peebles & Bothell, 2004;Seli et al, 2012b). Although these data certainly suggest that speed-accuracy trade-offs exist, given the correlational nature of the data, a number of other variables may also contribute to this outcome.…”
mentioning
confidence: 96%
“…This study showed that experience with net-speak helped to strengthen the link between the orthography of net-speak words and their meaning, but the link was not as strong as that between the orthography of conventional words and their meaning. In another study, Head et al (2012b) used the Go/No-Go task to explore the reaction time (RT) and accuracy (ACC) of college students in detecting "text" in a series of conventional words and "txt" in subset words. A 9-min detection task was divided into four continuous 2.25 min periods.…”
Section: Introductionmentioning
confidence: 99%
“…A solution to this problem is to use two different sustained attention tasks, where at least one does not require a confounding cognitive process, and examine the conjunction of each (relative to control conditions) [25]. Thus, although each test may require cognitive components in addition to sustained attention (e.g., simple rule maintenance and response inhibition in the SART [26], [27], [28], and counting in the tone task), sustained attention is the central component required in both tasks. This cognitive conjunction approach [25] enables us to isolate the common component (sustained attention) even though each individual task may have other cognitive demands.…”
Section: Introductionmentioning
confidence: 99%